AN APPLICATION OF THE POINT-DIPOLE MODEL TO THE PROBLEM OF OPTICAL ANOMALIES IN GRANDITE GARNETS - Shtukenberg A.G.; Popov D.Y.; Punin Y.O. (My University, 2002)
The origin of anomalous birefringence in grossular-andradite (grandite) garnets is considered. Using the point-dipole model we have calculated the anomalous optical indicatrix for four crystals (three from the paper by Takéuchi et al. (1982) and one studied previously by the present authors). The calculated indicatrix is in good agreement with the observed one. This suggests that the origin of anomalous birefringence in grandite garnets is due to Al/Fe ordering. Interrelations between the observed optical indicatrix, the structure of the growing face, the site occupancy in the crystal structure and the calculated optical indicatrix suggest a growth origin of Fe/Al ordering in grandite garnets and confirm the growth dissymmetrization hypothesis.